The enhancement on thermoluminescence response of rare earth metal-doped CaSO4/CaF2-based thermoluminescence dosimetry driven by polytetrafluoroethylene decomposition. (24th August 2018) - Nuraeni, N; Iskandar, F; Waris, A; Haryanto, F; Hiswara, E
Abstract: The effect of polytetrafluoroethylene (PTFE) addition and re-annealing treatment to thermoluminescence dosimeter (TLD) material such as CaSO4 :RE (rare earth dysprosium (Dy) or thulium (Tm)) was studied at different re-annealing temperatures. The x-ray diffraction pattern showed that CaF2 phase was observed together with CaSO4 :Dy at 500 °C, indicating a formation of CaSO4 /CaF2 :RE composite due to the reaction between CaSO4 and PTFE. Above 600 °C, the CaF2 phase become stronger than that of CaSO4 phase. The thermoluminescence (TL) peak of the composite was shifting from around 180 °C to around 140 °C as the re-annealing temperature increased from 600 to 800 °C, which correspond to TL characteristic of CaSO4 and CaF2 respectively. However, the maximum TL intensity occurred at re-annealing temperature of 700 °C. The results in this study indicate that the sensitivity of CaSO4 /CaF2 :RE TL response can be improved by controlling the crystallinity of the material as well as the ratio of CaSO4 and CaF2 in the composite.